PERANAN KOMISI PEMBERANTASAN KORUPSI (KPK) DALAM PEMBERANTASAN TINDAK PIDANA KORUPSI DI INDONESIA - saragi, paltiada; Washington Hasiholan, Andree (Honeste Vivere, 2025)
The increase of corruption now could not be categorized as common crime anymore but it had been an extraordinary crime. The way to wipe it out could not be done commonly too. It also demanded an extraordinary way. Law enforcement to remove the corruption done conventionally so far had various obstacles. Thus, extraordinary method of law enforcement was needed by forming a special committee that had a wide and independent authority and free from any power. The committee was KPK that was formed officially based on regulation No 30 year 2002. The normative role and function of KPK was doing investigation and prosecution on the case of corruption involving apparatus of law upholder, state operator, and other people who dealt with corruption case and dealt with nation loss at least Rp1.000.000.000,- (one billion rupiah). Besides having several strong points, in the practice of removing corruption, KPK also had many challenges; some of them were the working area of KPK that was too wide, the problem of relationship inter institution of corruption removing, and KPK socialization had not touched society.